Oxidative kinetic resolution of alcohols using chiral Mn-salen complex immobilized onto ionic liquid modified silica - Sahoo, Suman; Kumar, Pradeep; Lefebvre, F.; Halligudi, Shivaraj B. (Applied Catalysis A-General, 2009)
The supported ionic liquid strategy has been applied for the immobilization of chiral Mn(III) salen complex onto ionic liquid modified silica. Chiral Mn(III) salen complex was immobilized over silica through a thin film of covalently anchored imidazolium ionic liquid. These catalysts were characterized by N(2) sorption, XRD, MR, DRUV-vis, and elemental analysis. The results showed that the chiral Mn(III) salen complex could be successfully immobilized onto the modified mesoporous materials and that the long-range mesoporous ordering of parent supports was maintained after the immobilization. The immobilized catalyst provided good enantioselectivity and activity in the heterogeneous catalysis of the oxidative kinetic resolution of secondary alcohol and can be recovered and recycled for four times without obvious loss of enantioselectivity and activity. Oxidative kinetic resolutions of meso-diols, hydroxyl ester and primary alcohol were also studied using this catalyst system. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Mesoporous silica; Mn(III) salen; Oxidative kinetic resolution; Secondary alcohol; Supported ionic liquid